Tokyo boogie-woogie : Japan's pop era and its discontents - Nagahara, Hiromu (Harvard University Press, 2017)
Between the late 1920s and 1960s, Japan's recording industry produced songs that they simply labeled, "Popular Songs" (ryūkōka). Emerging within the context of the dramatic expansion of mass media during some of the most volatile decades in Japanese history, this musical genre came to occupy the mainstream of Japan's commercial music scene. Tokyo Boogie-Woogie is the first book-length, historical study in English of this musical phenomenon and its impact on the politics of culture in modern Japan. The book focuses on the broad range of self-appointed popular song critics, including musicians, intellectuals, political activists, and government officials, all of whom engaged in a series of contentious debates on these songs' cultural and social merits, or, more frequently, the lack thereof.--